A study on pollution sensitive sponge iron based production transportation model under fuzzy environment - Bhattacharya, Partha Pratim; Bhattacharya, Kousik; De, Sujit Kumar (Decision Making: Applications in Management and Engineering, 2022)
Over the last few years, sponge iron-based production transportation and pollution problems for major sponge iron producing countries are triggering a critical issue. The excess of marginal pollution from production industries and their disintegration takes drives towards the change of policymaking. The sustainable development of any country signifies the reduction of biohazards, which in turn improves the health index and livelihood status of people across the world. Keeping this in mind, a cost depreciation problem for the bi-layer integrated supply chain model has been built up. We consider the functional dependencies among all considerable decision variables like production rate, consumption rate which leads to the pollution rate of different countries exclusively. In this study, we have shown how production and rail freight transport relates to pollution. To draw several graphs and numerical computations we use MATLAB software and LINGO software via solution algorithm respectively. The comparative study has been presented using general fuzzy as well as cloudy fuzzy systems. Lastly, we have justified our proposed model using sensitivity analysis along with graphical interpretation.